Renal tubular dysfunction in patients with inflammatory bowel disease treated with aminosalicylate. Issue 6 (June 1997) - Schreiber, S; Hämling, J; Zehnter, E; Howaldt, S; Daerr, W; Raedler, A; Kruis, W
Abstract : BACKGROUND: An increasing number of case reports indicate potential nephrotoxicity of 5-aminosalicylic acid (5-ASA), which shares similarities with the chemical structures of both phenacetin and acetylsalicylic acid. AIM: In a point prevalence study the occurrence of sensitive indices indicative of early kidney malfunction was assessed in outpatients with inflammatory bowel disease. METHODS: Routine indices of kidney function (creatinine clearance, urinary protein content, pH, electrolytes, and microscopy) were investigated in 223 patients with inflammatory bowel disease as well as sensitive markers of glomerular or tubular dysfunction (microproteinuria by SDS polyacrylamide gel electrophoresis (SDS-PAGE), urinary concentrations of N-acetyl-beta-D-glucosaminidase, alpha 1-microglobulin, gamma-glutamyltransferase (GGT), alkaline phosphatase (AP), and albumin). Histories of exposure to 5-ASA were assessed by questionnaire. RESULTS: Patients receiving high amounts of 5-ASA, both actual as well as on a lifetime basis, showed an increased prevalence of tubular proteinuria by SDS-PAGE. Raised values for urinary AP and GGT indicate proximal tubular epithelial cells as the source. All other kidney function tests were normal. Analysis of covariates indicated strong associations between disease activity and size of 5-ASA doses as well as alterations in kidney tubular function. CONCLUSION: The possibility exists that high doses of 5-ASA may be associated with proximal tubular proteinuria. This point prevalence study cannot dissect the possible impact of chronic inflammation from high dose 5-ASA treatment and further prospective studies are warranted.